Realization of Zigbee Wireless Sensor Networks for Temperature and Humidity Monitoring - Helmy Fitriawan; Danny Mausa; Ahmad Surya Arifin; Agus Trisanto (IAES Indonesia Section, 2015)
Many physical phenomena and processes in theenvironment must be monitored. This problem can be solved withan ad-hoc wireless sensor network (WSN), which consists of anumber of small and self-power sensing devices (nodes) that areconnected with each other using effective wireless networks. Thispaper reports development of an embedded wireless sensornetwork (WSN) prototype for environmental parametersmonitoring. The network itself consists of a coordinator or datagateway which wirelessly collect temperature and humidity dataover several sensor nodes. Each sensor node is developed from anarduino based microcontroller, Xbee wireless module based onZigbee/IEEE 802.15.4 standards, and temperature and humiditysensor devices. In the prototype system, both temperature andhumidity sensors are calibrated with accurate instruments to obtainprecise measurements. Its communication functionality is alsotested in various network topologies. The battery lifetime iscalculated to predict the energy consumption. The testing resultsshow that the system works well in terms of its functionality.